The Relationship Between Self-Confidence And Future Anxiety In Early Adulthood - Dewi Zulaikhah; Sheilla Varadhila Peristianto; Zaskia Andini Ramli (Universitas Muhammadiyah Malang, 2026)
The level of anxiety about the future experienced in early adulthood varies from person to person, but self-confidence is part of the emotional and cognitive factors that protect against anxiety about the future. The purpose of this study was to determine the relationship between self-confidence and future anxiety in early adulthood. Early adulthood is a developmental phase characterized by major life transitions, increasing responsibilities, and uncertainty regarding career, relationships, and long-term life planning, which may heighten vulnerability to psychological distress. The research method used was quantitative, with data collected using a self-confidence scale and a future anxiety scale. The sample was selected based on accidental sampling with criteria of being between 18 and 40 years old and having a minimum education level of high school, resulting in 70 participants. Hypothesis testing used Spearman's rho correlation. The results indicated a negative correlation between the variables of self-confidence and anxiety with a sig. value (2-tailed) of 0.012 and a correlation coefficient value of -0.298. The hypothesis stating that there is a correlation between self-confidence and anxiety about the future in early adulthood was accepted. These findings emphasize the importance of developing psychological interventions that focus on increasing self-confidence, strengthening adaptive coping strategies, and enhancing emotional regulation as preventive measures in reducing anxiety about the future and improving overall psychological well-being.